АРАЛБОЙЫНДАҒЫ ХАБАР БЕРИЎ МИНАРЛАРЫНЫҢ ӨТМИШТЕГИ ӘҲМИЙЕТИ - Қанаатов, Е.Е. (ILIM hám JÁMIYET, 2022)
The article tells about the historical monuments of the X-XIII centuries in the Aral Sea region - the role of lighthouse towers for the life of the population in the past. The author gives interesting information about the characteristics of lighthouses located in the southeast of Ustyurt and on the Sultan-Uvais ridge along the banks of the Amu Darya.